2019
DOI: 10.1080/09291016.2019.1614749
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of naturally occurring bovine rotavirus infection in organized dairy farms, India

Abstract: An epidemiological study was conducted for detection of rotavirus by antigen ELISA kit in dairy calves from Central India (Madhya Pradesh and Chhattisgarh states) and North India (Uttar Pradesh state). Different epidemiological parameters like age, sex, parity, colour and consistency of faecal materials and seasonal changes in a year were recorded. A total of 816 faecal samples were screened and out of which 41 (5.02%) animals were found to be positive for rotavirus A. The higher prevalence was recorded in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 21 publications
(20 reference statements)
3
15
0
Order By: Relevance
“…Relationship between seasonal variations and rate of Rotavirus infection was studied and found that the percentage of infection was signi cantly higher in cold months (22.67%) than warm and hot months (7.27%). Similar results were reported by [4,8,11]. In Egypt, most calving occurs at the end of autumn and beginning of winter in which these neonatal calves are more susceptible to Rotavirus infection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Relationship between seasonal variations and rate of Rotavirus infection was studied and found that the percentage of infection was signi cantly higher in cold months (22.67%) than warm and hot months (7.27%). Similar results were reported by [4,8,11]. In Egypt, most calving occurs at the end of autumn and beginning of winter in which these neonatal calves are more susceptible to Rotavirus infection.…”
Section: Discussionsupporting
confidence: 87%
“…Increased risk of Rotavirus infection during cold months may be attributed to the increased survivability of virus at low relative humidity and temperature. Additionally, the titer of immunoglobulins such as IgA, IgM and IgG in colostrum which act as protective factor against such infection in calves was decreased in autumn, winter and increased during spring, summer [4,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enormous pathogens were incriminated as an etiologic agent of neonatal calves' enteritis. Rotavirus occupied the second grad of calves' enteropathogens following Escherichia coli causing intestinal villous atrophy ensuing malabsorption and maldigestion of the infected cases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many pathogens were implicated as pathogens-causing enteritis in neonatal calves. In enteric calves, co-infection is observed frequently, but a single etiology can also be the cause in some cases [4]. The prevalence of each pathogen may vary from farm to farm and region to region, based on herd size, age, sex, breed, season and animal hus-bandry practices [4].…”
Section: Introductionmentioning
confidence: 99%